Light passage through the polymer film of liquid crystal droplets with modified boundary conditions - Loiko, V.A.; Zyryanov, V.Ya.; Krakhalev, M.N.; Konkolovich, A.V.; Miskevich, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
A method to analyze coherent transmission coefficients and the small-angle
light scattering structure of PDLC layer with homogeneous and inhomogeneous
boundary conditions on the droplets surface is discussed. For PDLC films with
inhomogeneous boundary conditions at the polymer – liquid crystal interface, asymmetry
of the angular structure of light scattering with respect to the polar angle is revealed.
Besides, experimental results on transmittance are presented.